Effects of engaging fathers and bundling nutrition and parenting interventions on household gender equality and women's empowerment in rural Tanzania: Results from EFFECTS, a five-arm cluster-randomized controlled trial. (May 2023) - Galvin, Lauren; Verissimo, Cristiana K.; Ambikapathi, Ramya; Gunaratna, Nilupa S.; Rudnicka, Paula; Sunseri, Amy; Jeong, Joshua; O'Malley, Savannah Froese; Yousafzai, Aisha K.; Sando, Mary Mwanyika; Mosha, Dominic; Kumalija, Elfrida; et al.
Abstract: Advancing gender equality and women's empowerment (GE/WE) may contribute to better child nutrition and development in low-resource settings. However, few empirical studies have generated evidence on GE/WE and examined the potential of engaging men to transform gender norms and power relations in the context of nutrition and parenting programs. We tested the independent and combined effects of engaging couples and bundling nutrition and parenting interventions on GE/WE in Mara, Tanzania. EFFECTS (ClinicalTrials.gov, NCT03759821) was a cluster-randomized 2 × 2 factorial trial plus control. Eighty village clusters were randomly assigned to one of five intervention conditions: standard of care, mothers nutrition, couples nutrition, mothers bundled nutrition and parenting, or couples bundled nutrition and parenting. Between October 2018–May 2019, 960 households were enrolled with children under 18 months of age residing with their mother and father. Community health workers (CHWs) delivered a bi-weekly 24-session hybrid peer group/home visit gender-transformative behavior change program to either mothers or couples. GE/WE outcomes were analyzed as intention-to-treat and included time use, gender attitudes, social support, couples' communication frequency and quality, decision-making power, intimate partner violence (IPV), and women's dietary diversity (WDD). Data were collected from 957 to 815 mothers and 913 and 733 fathers at baseline and endline, respectively. Engaging couples compared to mothers only significantly increased paternal and maternal gender-equitable attitudes, paternal time spent on domestic chores, and maternal decision-making power. Bundling increased maternal leisure time, decreased maternal exposure to any IPV, and increased WDD over 7 days. A combination of engaging couples and bundling was most effective for paternal gender attitudes, couples communication frequency, and WDD over 24 h and 7 days. Our findings generate novel evidence that CHWs can deliver bundled nutrition and parenting interventions to couples in low-resource community settings that advance GE/WE more than nutrition interventions targeting only women. Highlights: We evaluated engaging fathers and bundling nutrition & parenting programs in TZ. Both interventions advanced gender equality and women's empowerment (GE/WE). We observed synergistic effects on GE/WE between bundling and engaging fathers. This is the first experimental evidence on engaging fathers, bundling, and GE/WE. Bundled nutrition-parenting programs can be gender-transformative and advance GE/WE.